Impact of cataract on health-related quality of life in a longitudinal Japanese chronic obstructive pulmonary cohort. (November 2018) - Irie, Hidehiro; Chubachi, Shotaro; Sato, Minako; Sasaki, Mamoru; Kameyama, Naofumi; Inoue, Takashi; Oyamada, Yoshitaka; Nakamura, Hidetoshi; Asano, Koichiro; Betsuyaku, Tomoko
Cigarette smoking increases the risk of developing both cataract and chronic obstructive pulmonary disease (COPD). The prevalence of cataract and the clinical characteristics of COPD patients with cataract were retrospectively investigated in a 2-year observational COPD cohort. We analyzed 395 patients with complete data on ophthalmologic evaluation (319 subjects with COPD and 76 subjects at risk of COPD). There was no difference in the prevalence of cataract between COPD patients and those at risk (47.0% vs. 42.1%, p = 0.44). Age ≥ 75 years, low body mass index, and hypertension were independently associated with cataract as a comorbidity in COPD. The incidence of exacerbation within 2 years was significantly higher in COPD patients with cataract than those without cataract (36.6% vs. 18.3%, p = 0.0019). COPD patients with cataract exhibited significantly higher COPD assessment test score compared to those without cataract (13.7 ± 8.9 vs. 11.5 ± 7.2, p = 0.0240). Overall St George's Respiratory Questionnaire score and each component were significantly worse in COPD patients with cataract compared to those without cataract. COPD patients with cataract exhibited poor health-related quality of life and frequent exacerbations. The association between cataract and exacerbations of COPD deserves further attention.